The Urgency of Determining the Post-Divorce Iddah Payment Period in Indonesian Religious Courts - Shofiatul Jannah; Roibin Roibin (Universitas Semarang, 2023)
This study aims to provide legal justice for women after divorce. The determination of the period of payment of iddah income after divorce by the ex-husband to the ex-wife is very important because women who are carrying out the iddah period are not allowed to leave the house. For this reason, husbands are encouraged to provide iddah as stated in the word of Allah surah al-Thalaq:1. But, after divorce, the man disappears regardless of his ex-wife, besides that the policy on determining the period of payment of iddah income has not been regulated in the legislation or the compilation of Islamic law. So this research is important to be carried out as an effort to realize justice for women. This research is a literature research (Library research), which is a study that presents a variety of data by the research topic which includes primary data, namely the concept of iddah in the compilation of Islamic law which will be analyzed using Islamic legal theory. The results of the study that the determination of the period of payment of income is very important to be stated in the laws and regulations in Indonesia. Because the obligation to practice iddah will also be carried out if the ex-wife does not experience any deficiency Even the state can determine sanctions for ex-husbands who do not provide iddah to ex-wives. Sanctions provide a deterrent effect and encourage husbands to comply with their obligations fairly and responsibly.